Effectiveness of Science E-Module Using Argument-Driven Inquiry Models to Improve Students' Generic Science, Critical Thinking and Scientific Argumentation Abilities - A A Sukarso; Amalia Syuzita; Susilawati (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to determine the effectiveness of e-module teaching materials with the Argument-Driven Inquiry model to improve students' generic science, critical thinking and scientific argumentation abilities. The development model design used is 4D which consists of the define, design, develop and disseminate stages. The e-module which was declared valid was then carried out on a limited scale trial on 27 students. Analysis of increasing generic skills in science, critical thinking and scientific argumentation using the n-Gain (g) test. The research results show that there is an increase in ability after the e-module is implemented into learning. The n-Gain value for generic science abilities is 68.70, critical thinking 62.25 and scientific argumentation 67.11. The n-Gain value for each variable is in the medium category so that the Argument-Driven Inquiry based science e-module is quite effective for use in science learning